β-Arrestin-mediated Signaling Regulates Protein Synthesis - DeWire, Scott M. (American Society for Biochemistry and Molecular Biology, 2008)
Seven transmembrane receptors (7TMRs) exert strong regulatory influences on virtually all physiological processes. Although it is historically assumed that heterotrimeric G proteins mediate these actions, there is a newer appreciation that β-arrestins, originally thought only to desensitize G protein signaling, also serve as independent receptor signal transducers. Recently, we found that activation of ERK1/2 by the angiotensin receptor occurs via both of these distinct pathways. In this work, we explore the physiological consequences of β-arrestin ERK1/2 signaling and delineate a pathway that regulates mRNA translation and protein synthesis via Mnk1, a protein that both physically interacts with and is activated by β-arrestins. We show that β-arrestin-dependent activation of ERK1/2, Mnk1, and eIF4E are responsible for increasing translation rates in both human embryonic kidney 293 and rat vascular smooth muscle cells. This novel demonstration that β-arrestins regulate protein synthesis reveals that the spectrum of β-arrestin-mediated signaling events is broader than previously imagined.